2020
DOI: 10.1002/14651858.cd013506
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulfate for acute exacerbations of chronic obstructive pulmonary disease

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows:To assess the e ects of magnesium sulfate for acute exacerbations of chronic obstructive pulmonary disease in adults. Magnesium sulfate for acute exacerbations of chronic obstructive pulmonary disease (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Thus the antiinflammatory, anti-cholinergic, and anti-histaminic actions of Mg 2? provide favorable effects in COPD conditions (Ni et al 2020). In a randomized, doubleblind trial, it is reported that infusion of magnesium could contribute in correction of altered parameters like functional respiratory capacity, inspiratory capacity, MIP and MEP in COPD patients (Skorodin et al 1995).…”
Section: Cystic Fibrosis Cystic Fibrosis Is An Autosomal Recessive Disorder Due To Mutation In the Cftr (Cystic Fibrosis Transmembrane Comentioning
confidence: 99%
“…Thus the antiinflammatory, anti-cholinergic, and anti-histaminic actions of Mg 2? provide favorable effects in COPD conditions (Ni et al 2020). In a randomized, doubleblind trial, it is reported that infusion of magnesium could contribute in correction of altered parameters like functional respiratory capacity, inspiratory capacity, MIP and MEP in COPD patients (Skorodin et al 1995).…”
Section: Cystic Fibrosis Cystic Fibrosis Is An Autosomal Recessive Disorder Due To Mutation In the Cftr (Cystic Fibrosis Transmembrane Comentioning
confidence: 99%
“…Moreover, the association between systemic inflammation and Mg deficiency has been delineated. Mg deficiency causes increases in serum levels of TNFα and inflammatory cytokines with a concomitant decline of production and release of anti-inflammatory cytokines [17][18][19][20][21][22]. Mg deficiency with its stressor effect makes the body more susceptible to physiological stress resulting in activation of the Hypothalamic-Pituitary-Adrenal (HPA) axis and sympathetic nervous system [23].…”
Section: Mg/mg Deficiency and Immune Systemmentioning
confidence: 99%
“…This may be the reason why hypomagnesemia is associated with impaired pulmonary function (4). Lower serum Mg concentrations are associated with an increased incidence of exacerbations in chronic obstructive pulmonary disease (COPD) (5)(6)(7)(8)(9). In view of these observations it is reasonable to assume that Mg deficiency would also worsen lung function in COVID-19.…”
Section: Mg and Lung Functionmentioning
confidence: 99%
“…Intravenous Mg sulfate, i.e. pharmacological Mg application, is emphasized as an adjunctive therapy for acute asthma in the emergency department (10) and discussed for acute exacerbations of COPD and asthma-COPD overlap (9). Whether intravenous Mg sulfate could improve lung function in COVID-19 has to be shown in controlled clinical trials.…”
Section: Mg and Lung Functionmentioning
confidence: 99%